Implementasi Sistem Web Terpadu untuk Koordinasi Pelayanan Transportasi Darat dan Laut - Husain, Hariati (Management of Information System Journal, 2024)
The increase in the number of people in cities is due to urbanization and high birth rates, resulting in an increase in the needs that must be met by cities. The process of recapitulation of transportation production data which is still carried out manually at the Gorontalo Land Transportation Management Center (BPTD) causes inefficiency and waste of resources, and is prone to errors. Ineffective communication between transportation service units hinders coordination and causes delays in data processing. In addition, the lack of data accessibility and transparency makes decision-making less optimal, and monitoring of operational performance becomes difficult. The current system is not in line with the advancement of information technology and is not flexible to adapt to future needs, and is not fully in accordance with government regulations and standards that demand efficiency and effectiveness in public services. Therefore, a website-based coordination application is needed to overcome inefficiencies, improve communication and coordination, and support better decision-making in transportation services. This research aims to improve the effectiveness of communication and coordination between transportation service units, increase data accessibility and transparency to support better decision-making, and improve the operational performance monitoring system by using the Waterfall method to describe the process of creating a system that is carried out linearly and sequentially, such as a waterfall that flows from one stage to the next. This study shows that the implementation of an integrated web system significantly improves efficiency and coordination in land and sea transportation services by facilitating real-time data integration, speeding up the decision-making process, and reducing the potential for operational errors. The results of the system trial showed a 30% improvement in service performance and a reduction in user wait time by up to 25%, which indicates the effectiveness of the system in simplifying workflows and improving customer satisfaction. It is hoped that the development of this website can increase the effectiveness and efficiency of the coordination of land and sea transportation services and provide an experience for users.